1984
DOI: 10.1002/jbm.820180105
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term compressive creep deformation and damage in acrylic bone cements

Abstract: Compressive creep tests were performed on five commercially available acrylic bone cements under conditions simulating in vivo usage. Measured creep strains are quite large, generally exceeding elastic strains. Large variations in creep response were noted among the various cements, with a carbon-reinforced cement by far the most resistant to creep. The empirical model epsilon = a exp(b sigma)tn was found to predict creep strains within about 10% of the measured values. Microscopic examination of some specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

1996
1996
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…A more probable explanation for this phenomenon is the occurrence of creep of the acrylic cement. Earlier studies have indicated that cement creeps [12][13]. Creep of the cement mantle, which is a timedependent phenomenon, would facilitate the subsidence of the taper with time without generating cement fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A more probable explanation for this phenomenon is the occurrence of creep of the acrylic cement. Earlier studies have indicated that cement creeps [12][13]. Creep of the cement mantle, which is a timedependent phenomenon, would facilitate the subsidence of the taper with time without generating cement fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental creep data were based on uniaxial tests, which considered the presence of only one stress component (Chwirut, 1984;Huiskes, 1994, 1995a). For this reason, the uniaxial creep laws could not be applied directly to structures with threedimensional stress states.…”
Section: The Finite Element Simulationsmentioning
confidence: 99%
“…Another problem which obstructed the direct use of the creep laws was the fact that they were determined assuming stress conditions which were either purely static (Chwirut, 1984), or cyclic dynamic Huiskes, 1994,1995a). However, assuming friction at the taper-cement interface, the stress state was neither purely static, nor cyclic dynamic (Fig, 3).…”
Section: The Finite Element Simulationsmentioning
confidence: 99%
See 2 more Smart Citations